How Facebook Shapes Public Perception and Attitude Towards Organizations in South Sudan: A Case Study of South Sudan Broadcasting Corporation Ssbc - Emmanuel Adigesi (Uganda Christian University, 2024)
The study examines the users’ generated content on Facebook at South Sudan Broadcasting corporation (SSBC). The study was guided by objectives which included; the online presence and activity of SSBC on Facebook and identifying the strategies to communicate effectively on Facebook among the workers and the youths at SSBC. This study investigates the influence of user-generated content on social media platforms, specifically Facebook, as well as on the opinions and perceptions of workers at South Sudan Broadcasting Corporation (SSBC). The research aims to identify the types of users-generated content that most effectively shape opinions and perceptions, and to determine the strategies that has been employed to leverage user-generated content for effective communication and collaboration among SSBC workers on selective exposure theory. A mixed-methods approach was used, combining both qualitative and quantitative data collection and analysis methods. The study will contribute to the existing body of knowledge on the impact of user-generated content on social media, and provide practical recommendations for organizations seeking to harness the power of user-generated content for effective internal communication and collaboration.
Undergraduate research